2016
DOI: 10.1167/iovs.16-19385
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Improves Functional and Structural Outcome of Retinal Injury Following Term Neonatal Hypoxia-Ischemia

Abstract: PURPOSE. The purpose of this study was to investigate the effects of sildenafil on retinal injury following neonatal hypoxia-ischemia (HI) at term-equivalent age in rat pups.METHODS. Hypoxia-ischemia was induced in male Long-Evans rat pups at postnatal day 10 (P10) by a left common carotid ligation followed by a 2-hour exposure to 8% oxygen. Shamoperated rats served as the control group. Both groups were administered vehicle or 2, 10, or 50 mg/kg sildenafil, twice daily for 7 consecutive days. Retinal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Sildenafil is well tolerated in children with idiopathic pulmonary arterial hypertension [11]. The effects of sildenafil have reported in infants and children [12][13][14][15][16][17][18]. Sildenafil increases foetal body-weight at birth [12] and intravenous sildenafil improves oxygenation in infants [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sildenafil is well tolerated in children with idiopathic pulmonary arterial hypertension [11]. The effects of sildenafil have reported in infants and children [12][13][14][15][16][17][18]. Sildenafil increases foetal body-weight at birth [12] and intravenous sildenafil improves oxygenation in infants [13].…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil increases foetal body-weight at birth [12] and intravenous sildenafil improves oxygenation in infants [13]. Treatment with sildenafil recovers neonatal retinal function and structure and these effects are dose dependent [14]. Oral sildenafil improves oxygenation index in infants with severe persistent pulmonary hypertension [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia and hypobaric nature in high-altitude (HA) area could cause pathologic changes in cardiovascular system, respiratory system and nervous system [1]. The retina is one of the most active tissues, hence pathological level of hypoxia may firstly cause functional and structural changes in retina [2][3][4][5][6][7][8]. Hemorrhages, cotton wool spots, and papilledema that occurred during acute exposure to HA environment are known as high-altitude retinopathy (HAR) [9][10][11].…”
Section: Backgroundsmentioning
confidence: 99%
“…This study is timely, as the ability of a cardiac dysfunction to predict the impact of hypoxic insults on neurological outcomes has been elusive, and these results may pave the way for new strategies to address the contribution of RV dysfunction to neurological injury and/or recovery. Recent studies have shown that agents that address RV function may be associated with brain recovery in animal models of HIE (5, 6). So far, two mechanisms of cardiac dysfunction have been described in neonates with a perinatal hypoxic insult: 1 ) depressed LV function from the initial insult that is further exacerbated by reactive oxygen species (from the reperfusion injury), leading to reduced normalQ. and pulmonary venous hypertension; and 2 ) hypoxia vasoconstriction of the pulmonary vascular bed, leading to elevated pulmonary vascular resistance and acute pulmonary hypertension physiology (3).…”
mentioning
confidence: 99%